Dynamic performance evaluation of rail fastening system based on a refined vehicle-track coupled dynamics model - Yuan, Xuancheng; Zhu, Shengyang; Zhai, Wanming (Vehicle system dynamics, 2022)
Damage of rail fastening system often occurs due to severe vehicle-track dynamic interactions. To evaluate the dynamic performance of the rail fastening system subject to dynamic interactions between vehicle and track, a refined vehicle-track coupled dynamics model involving an elaborated model of rail fastening clip (RFC) is developed in this work. Firstly, the RFC model is established based on the mode superposition method by which the difficulty in deducing dynamics equation due to the complex shape of RFC can be easily resolved. Then, the mode shape vectors and natural frequencies of RFC which required by the mode superposition method are obtained through a numerical modal analysis, and verified by a modal test. Finally, through the contact relationship between RFC and rail, the RFC model is implemented into the vehicle-track coupled dynamics model. The reliability of the proposed model is supported by a field test data, and the dynamic performances of rail fastening systems along the track subject to vehicle-track dynamic interactions can be efficiently and effectively evaluated. By applying the proposed model, the influences of rail corrugations, vehicle speeds, and rail pad stiffness on dynamic performances of the rail fastening system are evaluated in detail.